Influence of microscale turbulence on the phytoplankton of a temperate coastal embayment, Western Australia - Machado, D.; Marti, Clelia; Imberger, J. (Academic Press, 2014)
We investigated the influence of microscale turbulence on the large phytoplankton of a coastal embayment in south-western Australia. Microstructure, physical and fluorometric depth-profiling field measurements and water sampling for nutrient, chlorophyll-a analyses and counting of the large size fraction of phytoplankton (microphytoplankton) were conducted in late-winter and late-spring of 2012. In both seasons we observed dominance of diatoms, low numbers of dinoflagellates, low nutrient concentrations, nitrogen limitation, clear waters and high turbulence intensities. In late-winter, total nitrogen, chlorophyll-a and diatom cell concentrations were higher than in late-spring, but dinoflagellates abundance did not change substantially. This indicated that the chain-forming diatom life-forms that dominated (Leptocylindrus, Chaetoceros and Skeletonema) were able to utilize the increased pulses of nitrogen in late-winter. The prevailing turbulence intensities observed, associated with the wind speed, were such that the Batchelor scale was smaller than the length of the diatom chains (100-300µm), implying that these diatoms could experience microscale nutrient gradients. By contrast, the Kolmogorov velocity scales overwhelmed the motility abilities of the dinoflagellates observed, which in turn gain only little benefit from self propulsion at high turbulence. It is suggested that, nutrient storage allows diatoms surviving calm periods of low nutrient availability and formation of siliceous cell chains provide diatoms an advantage in accessing nutrients in turbulent coastal ecosystems. © 2014 Elsevier Ltd.